The Presence of Tertiary Lymphoid Structures Provides New Insight Into the Clinicopathological Features and Prognosis of Patients With Breast Cancer - Wang, Bin; Liu, Jie; Han, Yin; Deng, Yaotiao; Li, Jinze; Jiang, Yu (Frontiers in Immunology, 2022)
Background: Tertiary lymphoid structures (TLSs) have been proven to be predictive biomarkers of favorable clinical outcomes and response to immunotherapies in several solid malignancies. Nevertheless, the effect of TLSs in patients with breast cancer (BC) remains controversial. The objective of current study is to investigate the clinicopathological and prognostic significance of TLSs in BC. Given unique difficulties for detecting and quantifying TLSs, a TLS-associated gene signature based on The Cancer Genome Atlas (TCGA) BC cohort was used to validate and supplement our results. Methods: Ectronic platforms (PubMed, Web of Science, EMBASE, the Cochrane Library, CNKI and Wanfang) were searched systematically to identify relevant researches as of January 11, 2022. We calculated combined odds ratios (ORs) with 95% confidence intervals (CIs) to determine the relationship between clinicopathological parameters and TLSs. The pooled hazard ratios (HRs) and 95% CIs were also calculated to evaluate the prognostic significance of TLSs. The TLS signature based on TCGA BC cohort was applied to validate and supplement our results. Results: 15 studies with 3898 patients were eligible for enrollment in our study. The combined analysis indicated that the presence of TLSs was related to improved disease-free survival (DFS) (HR= 0.61, 95% CI: 0.41–0.90, p< 0.05) and overall survival (OS) (HR= 1.66, 95% CI: 1.26-2.20, p < 0.001). Additionally, the presence of TLSs was positively correlated with early tumor TNM stage and high tumor-infiltrating lymphocytes. TLS presence was positively related to human epidermal growth factor receptor 2 (HER-2) and Ki-67 but inversely correlated with the status of estrogen and progesterone receptor. Simultaneously, our study found that tumor immune microenvironment was more favorable in the high TLS signature group than in the low TLS signature group. Consistently, BC patients in the high TLS signature group exhibited better survival outcomes compared to those in the low TLS signature group, suggesting TLSs might be favorable prognostic biomarkers. Conclusions: TLS presence provides new insight into the clinicopathological features and prognosis in patients with BC. Whereas factors discussed limited the evidence quality of this study.